1985
DOI: 10.1136/bmj.290.6480.1463
|View full text |Cite
|
Sign up to set email alerts
|

Antibody guided irradiation of brain glioma by arterial infusion of radioactive monoclonal antibody against epidermal growth factor receptor and blood group A antigen.

Abstract: In a patient with recurrent grade IV glioma of the brain resistant to conventional treatment an antibody guided isotopic scan showed uptake by the tumour of a monoclonal antibody (9A) that was developed against epidermal growth factor receptor but cross reacted with

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0
3

Year Published

1986
1986
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 124 publications
(29 citation statements)
references
References 11 publications
0
26
0
3
Order By: Relevance
“…In contrast to anti-idiotypic antibodies, though, the anti-fusion junction peptide antibody may react, not with just one patient's tumor, but rather with the tumors of all patients with this particular EGFR deletion mutation. Immunoimaging and immunotherapy have been performed with antibodies reactive against brain tumors, including antibodies reactive against the intact EGFR in gliomas (27,28). However, the molecules thus far targeted in brain tumors, such as the intact EGFR, are also expressed by normal tissues, thereby limiting the amount of antibody delivered to tumor and potentially leading to normal tissue toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to anti-idiotypic antibodies, though, the anti-fusion junction peptide antibody may react, not with just one patient's tumor, but rather with the tumors of all patients with this particular EGFR deletion mutation. Immunoimaging and immunotherapy have been performed with antibodies reactive against brain tumors, including antibodies reactive against the intact EGFR in gliomas (27,28). However, the molecules thus far targeted in brain tumors, such as the intact EGFR, are also expressed by normal tissues, thereby limiting the amount of antibody delivered to tumor and potentially leading to normal tissue toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…Study of this is currently hampered by the lack of immunological reagents which reliably detect EGF receptor expression in paraffin embedded archival material. The high levels of receptor expression do however provide a target for immunoscintigraphy (Takahashi et al, 1987) and immunotherapy (Epenetos et al, 1985;Kalofonos et al, 1989) and novel forms of receptor inhibitors (Gullick, 1990 (Slamon et al, 1989;Gullick et al, 1990), stomach (Falck & Gullick, 1989) and ovarian cancers (Slamon et al, 1989) and with a lower frequency in other tumour types (Hall et al, 1990;Yokota et al, 1986;Lemoine et al, 1990b). The c-erbB-2 protein, detected by Western blotting, was expressed at low, variable levels in the cell lines, but not in the primary tumour biopsies.…”
Section: Egf Receptormentioning
confidence: 99%
“…2,18,27 Several tumor clinical trials have shown that localization of monoclonal antibodies to the brain is poor without BBBD (0.0006%-0.0043% of the injected dose/ gram of tumor). 4,8,13,17,25,26 There is also evidence of a 20-fold increase in permeability to immunoreactive immunoglobulin M monoclonal antibody with BBBD in rats. 17 Based on these findings, BBBD may also significantly increase delivery of bevacizumab to the brain.…”
Section: Blood-brain Barrier Disruptionmentioning
confidence: 99%